Fraction distribution of cadmium in surface sediment collected from bivalve species harvesting areas in Binh Thuan province (Tuy Phong, Phan Thiet, Lagi) - Nguyen Cong, Thanh; Thien, Luu Ngoc; Nguyen Thi , Hue (Vietnam Journal of Marine Science and Technology, 2023)
This paper aims to provide information about the fractions of cadmium (Cd) and its distribution in surface sediment collected from bivalves harvesting areas in Binh Thuan province (Tuy Phong, Phan Thiet, Lagi). For this purpose, the sediment samples were collected monthly along with these areas in 2015–2016. To analyze the fractions of Cd, a five-step Tessier (1979) sequential extraction process was used, including Fraction 1 (Exchangeable), Fraction 2 (Bound to carbonate), Fraction 3 (Bound to iron-manganese oxide), Fraction 4 (Bound to organic compounds), and Fraction 5 (Residual). The research showed that Cd concentrations contributed mainly to a strong association residual fraction (Fraction 5). However, the percentage of Cd in total Fraction 1 and Fraction 2 (high mobility and bioavailability fractions) in all areas was also relatively high. In the Tuy Phong and Lagi harvesting areas, the sediment distribution follows the trend of F5 > F2 > F3 > F4 > F1, while the trend present in sediment in the Phan Thiet harvesting area follows F2 > F5 > F3 > F1 > F4. The Fractions F1, F4, and F5 indicated a weak positive correlation with the total concentration of Cd, while F3 and F2 indicated medium and strong correlations, respectively. According to the Risk Assessment Code (RAC), the results reveal that Cd poses a high environmental risk in this area.